2021
DOI: 10.3390/su13031427
|View full text |Cite
|
Sign up to set email alerts
|

Faux Fur Trade Networks Using Macroscopic Data: A Social Network Approach

Abstract: This study used social network analysis, which is often adopted to analyze changes in trade structures and the world trade network for faux fur products, which are alternative materials used in vegan fashion. The data on the total trade value of artificial fur (HS Code: 4304) and animal fur and leather (HS Code: 0505) imports and exports between countries were collected through UN Comtrade, and the degree and betweenness centralities were used to analyze the trade structure of faux fur in 2009, 2014, and 2019 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Centrality analysis defines the meanings of each keyword in the context of a document (Choi et al, 2021 ), which are indicated in terms of degree, betweenness, closeness, and eigenvector centrality (Kwahk, 2014 ), as shown in Eqs. 2 – 5 .…”
Section: Methodsmentioning
confidence: 99%
“…Centrality analysis defines the meanings of each keyword in the context of a document (Choi et al, 2021 ), which are indicated in terms of degree, betweenness, closeness, and eigenvector centrality (Kwahk, 2014 ), as shown in Eqs. 2 – 5 .…”
Section: Methodsmentioning
confidence: 99%
“…Studies utilizing network analysis have been conducted on global trade contexts [ 13 18 ], intra-African countries [ 19 ], ASEAN countries [ 15 , 20 ], OECD countries [ 21 ], China, BRIC, and African countries [ 22 , 23 ], Latin American countries [ 24 ], Shanghai Cooperation Organization countries [ 25 ], and Central Asia and Caucasus countries [ 26 ]. Furthermore, these studies focus on general trade [ 15 , 17 19 , 21 , 22 , 24 – 27 ], energy [ 13 , 14 , 16 , 23 , 28 ], food [ 29 31 ], clothing [ 32 , 33 ], and electronic products [ 4 ]. However, to the best of our knowledge, no studies have examined electronic product trade at the country group level during the COVID-19 period using complex network and panel data analyses.…”
Section: Introductionmentioning
confidence: 99%